Mature Anterior Mediastinum Teratoma Manifesting as a Neck Mass in an Adult Male: A Rare Case Report - Setiawati, Dea Alberta; Soewoto, Widyanti (http://dharmais.co.id/, 2026)
Introduction: Mediastinum tumors are a group of tumors that grow in the mediastinum. Teratomas of the anterior mediastinum are a rare case in adulthood, accounting for only 1-3% of all teratomas. While mature teratoma in the mediastinum is typically benign, it can grow significantly large and invade vital structures such as the esophagus and trachea, and can be misdiagnosed as a neck mass. This case highlights the importance of thorough evaluation in diagnosing mediastinum tumors that involve both the cervical and thoracic regions to prevent misleading diagnoses.Case Presentation: This report discusses the case of a 33-year-old male initially diagnosed with a thyroid tumor. However, upon further examination, it was found that the mass originated from the anterior mediastinum, compressing and displacing the trachea, esophagus, and thyroid gland, necessitating surgical excision involving a multidisciplinary team. In addition to the removal of the tumor, partial esophageal wall excision and a gastrostomy procedure were performed to maintain nutritional flow during the healing process.Conclusions: Mature teratoma in the anterior mediastinum can cause compression and invasion of vital structures. A thorough evaluation in diagnosing mediastinum tumors that involve both the cervical and thoracic regions should be done. This case underscores the need for a multidisciplinary approach to prevent misdiagnosis and long-term follow-up to monitor the potential for recurrence or malignant transformation in patients with mediastinal tumors.